Towards a methodology for optimizing indicator indicators of the working process of diesel locomotive diesel engines - Ablyalimov Oleg (E3S Web of Conferences)
A methodology is proposed for substantiating the optimal parameters of the turbocharger and air cooler of a two-stroke diesel locomotive diesel engine with air supercharging when its diesel generator set operates in partial modes. The resulting analytical expressions and graphical dependencies are intended to optimize the indicator indicators of the working process of diesel engines under operating conditions of diesel locomotives, taking into account the intermediate positions of the driver’s controller in a wide range of changes in the temperature of the charge air and of the environment. It is recommended to continue these theoretical studies in order to optimize the indicator indicators of the working process of four-stroke diesel locomotive diesel engines under similar operating conditions.